ANALYZING COLONIAL REMNANTS: A COMPARATIVE ANALYSIS OF INDONESIAN ECONOMIC DEVELOPMENT (1950–1980) - Manlee, Chrystle Feodore; Kurniawan, Fransisca Elvanty (Universitas Pelita Harapan, 2024)
The Global South has always been a running contributor to the global inequality index, becoming a threat to international stability and sustainability. In most cases, it is found that colonial dependency is one major factor that causes this hindrance in development, leading to inequality. In its journey to independence, Indonesia had undergone a strict economic system under Dutch colonialism, and further transitioned to two different governing systems before its reformation, producing different outcomes of economic policy management and spread of inequality. Thus, this research wishes to understand the differences of economic system governance between the Soekarno and Soeharto era, and whether they possess any remnants of colonial dependency integrated within them. The Dependency Theory is used in this research with the concepts of postcolonialism, development, and inequality embedded into the discussions. The data of this research is gathered through academic literature, utilizing a qualitative approach, and is conducted with a descriptive and historical comparative approach. This research finds that Dutch colonialism contributed a major role in how Indonesia manages its economic strategies and how it impacts its high social and economic inequality. Further stretching to post-independence, it is found that Soekarno's decoupling of Western values translated worse into the economy, compared to Soeharto's Western-centric approaches to trade. The root causes of colonial dependencies and habits affect the outcome of economic habits, and thus contribute to the efficiencies of how Indonesia manages its economy during the period before reformation.